An Application of Adaptive Blades on Convertible MAVs. Issue 4 (December 2013) - Lv, Peng; Mohd-Zawawi, Fazila; Benard, Emmanuel; Prothin, Sebastien; Moschetta, Jean-Marc; Morlier, Joseph
A passive twist control is considered as an adaptive way to maximize the overall efficiency of a proprotor developed for convertible Micro Air Vehicles. The varied operation conditions suggest different twist distributions for hover and forward flight with the constraint of identical planform. In this work, adaption of the proprotor geometry is achieved by centrifugal force induced twist. Classical Lamination Theory is used to predict structural loads, while Blade Element Momentum Theory is employed to understand the aerodynamic benefits of adaptive proprotor as applied on Micro Air Vehicles. Tip mass is proposed to increase the stability and generate negative torsion for rotating blade. Validation of the procedure is based on measurements of blade deformation, performed by laser displacement sensors. While negative torsion is found in both rotor and propeller modes, level of deformation is still below what is required for optimum dual operation.